The Heroic White Man and the Fragile Asian Girl: Racialized and Gendered Orientalism in Olympic Figure Skating. Issue 7 (24th May 2019) - Oh, Chuyun
Abstract: Intersecting performance studies and critical sports studies, this article analyzes the North American media coverage of South Korean figure skater and the gold medalist Yuna Kim at the 2010 Winter Olympics in Vancouver. While North American newspapers and NBC (US) and CTV (Canada) broadcasts acclaim Kim's athletic achievements onstage, they also infantilize and Orientalize Kim as an exotic, fragile, and dependent Asian girl. Contrarily, the media highlights the role of her Canadian coach Brian Orser offstage as a heroic white man. It dramatizes and sympathetically identifies with him by nostalgically recalling the 'Battle of the Brians'. When Kim's Koreanness is invisible and conflated as hypervisible ethnic Other, Asian/Asian Americanness, her athletic competency is negated under the name of Orientalism that fetishizes, romanticizes, and thus, reinforces the racialized and gendered hierarchies between the heroic white man and the fragile Asian girl. Nevertheless, Asian/Asian American female athletes' increased visibility opens a liberatory space for re-visiting Asian and Asian Americanness – Pan-Asian identity – at the glocal Olympic stage.